Vous êtes sur la page 1sur 59

 K n C K[X] K[X] C[X] R[X] R R

 C n

3 > 1 1 > 3 1 + 1 = 3

P P ¬P P P P ¬P

P
¬P
V
F
F
V

3 > 4 3 4

P Q

P Q P Q P Q P Q

P Q

P Q P Q P Q P Q P Q P Q P Q P Q P

 P Q P ∧ Q P ∨ Q P ⇒ Q V V V V V V F F V F F V F V V F F F F V

P 2 Q 3|7 P Q F P Q V P Q F Q P V

P Q P

Q P Q

P P Q

P ∨ ¬P

P Q (P Q)(Q P ) P

Q

P Q

 ¬(¬P ) ⇔ P

(P Q) (¬P Q)

((P Q) (Q R)) (P R)

 ((P ⇒ Q) ⇔ (¬Q ⇒ ¬P ) (P ⇒ Q) ∧ (¬P ⇒ Q) ⇒ Q

Q P P Q Q Q P P Q P Q P Q Q Q

N n n 2

N n 2 n

2

¬(P Q) P (¬Q)

b f (x)dx 0

f [a, b] f 0 [a, b]

a

x x 2 Q

x + 3 = 2 x P (x) , , !

x, P (x) x P (x) P (x) x x, P (x) x P (x) P (x) x ! x, P (x) x P (x) P (x) x

f f : I R f x I, f (x) = 0

f

¬(x, P (x)) (x, ¬P (x))

¬(x, P (x)) (x, ¬P (x))

 ∀ x ∈ R, x 1 ∀ x ∈ R, ∃ n ∈ Z, n x < n + 1 ∃ x ∈ N, x ∈ R ∃ n ∈ Z, ∀ x ∈ R, n x < n + 1

3 4

S lim n+ u n l l ]l , l + [ u n ]l , l+ [ n

MT 11

> 0, N, n N ⇒ |u n l| <

x E x E x E

A = {1, 2, 3}

B = {

C = {n N, 7 | n n 2 > 1000}

E F

> 1}

 E F E ⊂ F ∀x x ∈ E ⇒ x ∈ F E F E = F ∀x x ∈ E ⇔ x ∈ F

E = ∅ ⇔ ∀x, x / E

E = {n N , n 2 < 0} ⇒ E =

N Z Q R C

E, ∅ ⊂ E

E F E F F E

E F

E F E F E F (x E F ) (x E) (x F )

E F E F E F (x E F ) (x E) (x F )

E F E \ F E F (x E \ F ) (x E) (x / F )

F E F E C E F F c F E

E \ F

E × F (e, f ) e E f F

{1, 3, 5} ∪

{2, 3, 4} = {1, 2, 3, 4, 5}

 {1, 3, 5} ∩ {2, 3, 4} = {3} {1, 3, 5} \ {2, 3, 4} = {1, 5} {1, 2} ⊂ {1, 2, 3, 4} {1, 2} = {3, 4} {1, 3, 5} × {2, 3, 4} = {(1, 2); (1, 3); (1, 4); (3, 2); (3, 3); (3, 4); (5, 2); (5, 3), (5, 4)}

E × F

E E Card(E) E E

= F × E

E F Card(E × F ) = Card(E) × Card(F )

E F F E F = F

A = nN [ n , 2008 n ] B = nN ] n , 2008 +

1

1

1

1

n [

F E

P(E) E P(E) E

E P(E)

E F

F

E = { , } P(E) = {∅, { }, { }, E}

3 {3}

R P(R)

Card(E) = n Card(P(E)) = 2 n

Y = {x, x

x}

(Y Y ) (Y

Y )

11

E F G

f E F (E, F, Γ) Γ E × F

x E, !y F, (x, y) Γ.

(x, y) Γ y = f (x) y x f x y f E F Γ E × F f

F E E F R N N R

f : E F G E E g : G F x G g(x) = f (x) g f G f g

f :

R

x

E Id E Id E

E

x

R +

x

2

R R +

E

x

V f

f :

V

v

R + || v||

f : E F g : F G f g g f : E G x E g(f (x))

f g

=

g f

f

E

F (E, F, Γ) D E

Γ D × F

x D, !y

F, (x, y) Γ D

f E F f F F F

 f ⇔ ∀x ∈ E ∀y ∈ E f (x) = f (y) ⇒ x = y f ⇔ ∀y ∈ F, ∃x ∈ E f (x) = y f ⇔ ∀y ∈ F, ∃!x ∈ E f (x) = y

f f

f :

V

v

f :

R

x

f :

R +

x

[2, +[ x 2 + 2

R + || v||

R + x 2 +

2

R[X] φ :

R[X] R[X]

P

P

φ

f E F A E A f f (A)

f (A) = {y F, x A, y = f (x)}.

B F B f f 1 (B)

f 1 (B) = {x E, f(x) B}.

f :

f :

R R

x

P

(x, y)

x

A = [0, 125π ] A = f(A)

3

P

(x, 0)

∆ = (Ox) = (Oy) f (∆) f (∆ )

sin 1 ({1})

f :

R

x

R

x 2

B = [0, 9] f 1 (B)

B 1 = [4, 16] B 2 = [9, 25]

f

f

1

1

(B 1 ) (B 1 )

 ∪ f −1 (B 2 ) f −1 (B 1 ∪ B 2 ) ∩ f −1 (B 2 ) f −1 (B 1 ∩ B 2 )
 f(f −1 (B 1 )) B 1 f −1 (f(B 2 )) B 2

f 1 f : E F f 1 y F f f 1 f = Id E f f 1 = Id F

f : E F

f

⇔ ∃ g : F

E f g = Id F

g f = Id E

E F E F

E F (E, F, Γ) Γ E × F E F Γ E × F (x, y) Γ x y xRy

f : E F E F

E E F = E E E

N nRm n|m

V vRw

v.w = 0

R E E R x E, xRx R (x, y) E 2 , xRy yRx R (x, y, z) E 3 , (xRy) (yRz) xRz

R

2π

Z aRb 5|(a b)

N 2 (n, m)R(n , m ) n + m = n + m

E R x E

x = {y E|xRy}

(O, i, j)

(Ox) ∆ = { y = k, k R}

R E x y E x y x y

E E

=

x

x y

= ∅ ⇒ x = y

E = xE x

E R E/R E R

E/R = {x|x E}.

[2π] 2π R/[2π] = [0, 2π[

R Z xRy 5|(x y) Z/R = {0, 1, 2, 3, 4}

n N Z R xRy n|(x y)

R

x Z x x x y = ∅ ⇔ x

Z/nZ

= y

E R R x E, xRx R (x, y) E 2 , (xRy) (yRx) x = y R (x, y, z) E 3 , (xRy) (yRz) xRz

R P(N) P(E) aRb a|b N Z

R E E

(x, y) E 2 xRy yRx.

E

(R, ) (P(E), )

R 2

R N nRm n | m (N , R)

P (O, u, v) O G

G = {r O,θ , θ}

G × G G

G × G

(r O,θ 1 , r O,θ 2 )

G

r O,θ 1 r O,θ 2 = r O,θ 1 +θ 2

E E E × E E (x, y) z x y

O

(r O,θ 1 r O,θ 2 ) r O,θ 3 =

r O,θ 1 (r O,θ 2 r O,θ 3 )

E x, y, z E (x y) z = x (y z)

e O θ = 0 r O,θ e = e r O,θ = r O,θ

E e x E ex = xe = x

θ R r O,θ r O,θ = r O,θ r O,θ = e r O,θ

E e y x x y = y x = e

r O,θ 1 r O,θ 2

= r O,θ 2 r O,θ 1

(x, y) E 2 x y = y x

(N, +) (R, +) (R, ×) (C, +) (C, ×)

G

x G

x G x

. x 1 x + x x

(Z, +) (R, +) (N, +) (Z, ×)

R − {1} x y = x + y xy

ABC ABC ABC ABC 6

G x y G

 (xy = xz) ⇒ y = z (yx = zx) ⇒ y = z (xy) −1 = y −1 x −1 xy = yx (xy) n = x n y n

G = Z/nZ G

aRb n|(a b).

(Z/nZ, +)

(G, ) H G G H

(Z, +) n N nZ = {b Z, b = na, a Z} (Z, +)

+ Z/nZ x+y

=

x + y

+

(G, ) {e G } G G

(G, ) H G

H

(x, y) H 2 x y H x H x 1 H

H

H G H G H

= (x, y) H 2 xy 1 H

G G G

Z nZ n N

(G, ) (F, .) f : G F f (x y) = f (x).f (y) x y G

exp

(R, +)

x

(R + , ×) exp(x)

f : (G, ) (F, .) e G e F G F

 f (e G ) = e F ∀x ∈ G f (x −1 ) = f(x) −1

f : (G, ) (F, .)

H G f (H) F

H F f 1 (H ) G

f : (G, ) (F, .) f 1 ({e F }) f ker(f )

f : (G, ) (F, .)

f ker f = e G

f Imf = F Imf f (G)

f : (G, ) (F, .) f

A + .